2013
DOI: 10.1016/j.jcmg.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeled WBC Scintigraphy in the Diagnostic Workup of Patients With Suspected Device-Related Infections

Abstract: (99m)Tc-HMPAO-WBC scintigraphy enabled the confirmation of the presence of CIED-associated infection, definition of the extent of device involvement, and detection of associated complications. Moreover, (99m)Tc-HMPAO-WBC scintigraphy reliably excluded device-associated infection during a febrile episode and sepsis, with 95% negative predictive value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
1
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(102 citation statements)
references
References 33 publications
1
91
1
9
Order By: Relevance
“…[ 18 F]FDG PET/CT in association with Duke criteria also allowed reclassifying most of cases initially classified as¨possible¨IE [18]. Erba et al also reported a good diagnostic accuracy (94%) of 99m TC-HMPAO WBC SPECT/CT for CIED infection and for distinguishing infection limited to the pocket or leads from a more severe infection affecting the whole device [23] (Table 2). Therefore, both imaging approaches can be of help in patients with suspected CDRIE (ESC class IIb recommendations) [5].…”
Section: Cardiac Device-related Iementioning
confidence: 99%
“…[ 18 F]FDG PET/CT in association with Duke criteria also allowed reclassifying most of cases initially classified as¨possible¨IE [18]. Erba et al also reported a good diagnostic accuracy (94%) of 99m TC-HMPAO WBC SPECT/CT for CIED infection and for distinguishing infection limited to the pocket or leads from a more severe infection affecting the whole device [23] (Table 2). Therefore, both imaging approaches can be of help in patients with suspected CDRIE (ESC class IIb recommendations) [5].…”
Section: Cardiac Device-related Iementioning
confidence: 99%
“…Cep infeksiyonuna sıklıkla "lead" tutulumu eşlik etmiştir. 26 Sintigrafisi negatif olan hiçbir hastada, 12 aylık izlemide cihaz enfeksiyonu gelişmemiştir. Duke kriterlerinin duyarlılığı ise %77 olarak bildirilmiştir.…”
Section: Manyeti̇k Rezonans Görüntülemeunclassified
“…Ateş ve sepsis tablosunda, lökosit sintigrafisiyle İK cihaz enfeksiyonu %95'lik negatif prediktif değerle dışlanmıştır. 26 Protez kapak veya İK cihaz enfeksiyonu tanı-sında 18 F-floro-deoksiglikoz (FDG)-PET/BT kullanılarak pek çok çalışma yapılmıştır. 23,24,[27][28][29] Protez kapaklı 72 hastalık bir çalışmada, Duke kriterlerine, anormal FDG tutulumun eklenmesiyle duyarlılık %70'den %97'ye çıkmıştır.…”
Section: Manyeti̇k Rezonans Görüntülemeunclassified
See 2 more Smart Citations